OP0018 A MULTICENTER RANDOMIZED STUDY IN EARLY RHEUMATOID ARTHRITIS TO COMPARE ACTIVE CONVENTIONAL THERAPY VERSUS THREE BIOLOGICAL TREATMENTS: 24 WEEK EFFICACY RESULTS OF THE NORD-STAR TRIAL. (2nd June 2020) - Hetland, M. L.; Haavardsholm, E. A.; Rudin, A.; Nordström, D.; Nurmohamed, M.; Gudbjornsson, B.; Lampa, J.; Hørslev-Petersen, K.; Uhlig, T.; Gröndal, G.; Ǿstergaard, M.; Heiberg, M.; et al.
Abstract : Background: The optimal first-line treatment of patients (pts) with early rheumatoid arthritis (RA) is yet to be established. Objectives: The primary aim was to assess and compare the proportion of pts who achieved remission with active conventional therapy (ACT) and with three different biologic therapies after 24 wks. Secondary aims were to assess and compare other efficacy measures. Methods: The investigator-initiated NORD-STAR trial (NCT01491815 ) was conducted in the Nordic countries and Netherlands. In this multicenter, randomized, open-label, blinded-assessor study pts with treatment-naïve, early RA with DAS28>3.2, and positive RF or ACPA, or CRP >10mg/L were randomized 1:1:1:1. Methotrexate (25 mg/week after one month) was combined with: 1) (ACT): oral prednisolone (tapered quickly); or : sulphasalazine, hydroxychloroquine and mandatory intra-articular (IA) glucocorticoid (GC) injections in swollen joints <wk 20; 2) certolizumab 200 mg EOW SC (CZP); 3) abatacept 125 mg/wk SC (ABA); tocilizumab 162 mg/wk SC (TCZ). IA GC was allowed in all arms <wk 20. Primary outcome was clinical disease activity index remission (CDAI≤2.8) at wk 24. Secondary outcomes included CDAI remission over time and other remission criteria. Dichotomous outcomes were analyzed by adjusted logistic regression with non-responder imputation (NRI). Non-inferiority analyses had a pre-specified margin of 15%. Results: 812 pts were randomized. Age was 54.3±14.7 yrs (mean±SD), 31.2% were male, DAS28 5.0±1.1, 74.9% were RF and 81.9% ACPA positive. Fig 1 shows the adjusted CDAI remission rates over time with 95% CI. Table shows crude remission and response rates and absolute differences in adjusted remission and response rates (superiority analysis). Differences in remission and response rates with CZP and TCZ, but not with ABA, remained within the pre-defined non-inferiority margin versus ACT, Fig 2 . Conclusion: High remission rates were found across all four treatment arms at 24 wks. Higher CDAI remission rate was observed for ABA versus ACT (+9%) and for CZP (+4%), but not for TCZ (-1%). With the predefined 15% margin, ACT was non-inferior to CZP and TCZ, but not to ABA. This underscores the efficacy of active conventional therapy based on MTX combined with glucocorticoids and may guide future treatment strategies for early RA. Acknowledgments: Manufacturers provided CZP and ABA. Disclosure of Interests: Merete L. Hetland Grant/research support from: BMS, MSD, AbbVie, Roche, Novartis, Biogen and Pfizer, Consultant of: Eli Lilly, Speakers bureau: Orion Pharma, Biogen, Pfizer, CellTrion, Merck and Samsung Bioepis, Espen A Haavardsholm Grant/research support from: AbbVie, UCB Pharma, Pfizer Inc, MSD Norway, Roche Norway, Consultant of: Pfizer, AbbVie, Janssen-Cilag, Gilead, UCB Pharma, Celgene, Lilly, Paid instructor for: UCB Pharma, Speakers bureau: Pfizer, AbbVie, UCB Pharma, Celgene, Lilly, Roche, MSD, Anna Rudin Consultant of: Astra/Zeneca, Dan Nordström Consultant of: Abbvie, Celgene, Lilly, Novartis, Pfizer, Roche and UCB., Speakers bureau: Abbvie, Celgene, Lilly, Novartis, Pfizer, Roche and UCB., Michael Nurmohamed Grant/research support from: Not related to this research, Consultant of: Not related to this research, Speakers bureau: Not related to this research, Björn Gudbjornsson Speakers bureau: Novartis and Amgen, Jon Lampa Speakers bureau: Pfizer, Janssen, Novartis, Kim Hørslev-Petersen: None declared, Till Uhlig Consultant of: Lilly, Pfizer, Speakers bureau: Grünenthal, Novartis, Gerdur Gröndal: None declared, Mikkel Ǿstergaard Grant/research support from: AbbVie, Bristol-Myers Squibb, Celgene, Merck, and Novartis, Consultant of: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo Nordisk, Orion, Pfizer, Regeneron, Roche, Sandoz, Sanofi, and UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo Nordisk, Orion, Pfizer, Regeneron, Roche, Sandoz, Sanofi, and UCB, Marte Heiberg: None declared, Jos Twisk: None declared, Simon Krabbe: None declared, Kristina Lend: None declared, Inge Olsen: None declared, Joakim Lindqvist: None declared, Anna-Karin H Ekwall Consultant of: AbbVie, Pfizer, Kathrine L. Grøn Grant/research support from: BMS, Meliha C Kapetanovic: None declared, Francesca Faustini: None declared, Riitta Tuompo: None declared, Tove Lorenzen: None declared, Giovanni Cagnotto: None declared, Eva Baecklund: None declared, Oliver Hendricks Grant/research support from: Pfizer, MSD, Daisy Vedder: None declared, Tuulikki Sokka-Isler: None declared, Tomas Husmark: None declared, Maud-Kristine A Ljosa: None declared, Eli Brodin: None declared, Torkell Ellingsen: None declared, Annika Soderbergh: None declared, Milad Rizk Speakers bureau: AbbVie, Åsa Reckner: None declared, Per Larsson: None declared, Line Uhrenholt Speakers bureau: Abbvie, Eli Lilly and Novartis (not related to the submitted work), Søren Andreas Just: None declared, David Stevens: None declared, Trine Bay Laurberg Consultant of: UCB Pharma (Advisory Board), Gunnstein Bakland Consultant of: Novartis, UCB, Ronald van Vollenhoven Grant/research support from: BMS, GSK, Lilly, UCB, Pfizer, Roche, Consultant of: AbbVie, AstraZeneca, Biogen, Biotest, Celgene, Gilead, Janssen, Pfizer, Servier, UCB, Speakers bureau: AbbVie, Pfizer, UCB